Anterior cingulate gyrus acts as a moderator of the relationship between problematic mobile phone use and depressive symptoms in college students. Issue 5 (1st February 2021) - Zou, Liwei; Wu, Xiaoyan; Tao, Shuman; Yang, Yajuan; Zhang, Qingjun; Hong, Xuedong; Xie, Yang; Li, Tingting; Zheng, Suisheng; Tao, Fangbiao
Abstract: This study aimed to investigate the brain grey matter volume (GMV) related to problematic mobile phone use (PMPU), and whether these regions of GMV play a potential moderating role in the relationship between PMPU and depressive symptoms. We recruited 266 students who underwent magnetic resonance imaging (MRI) scanning. PMPU and depressive symptoms were assessed by a self-rating questionnaire for adolescent PMPU and patient health questionnaire-9, respectively. A multiple regression model was performed to detect GMV and white matter (WM) integrity associated with PMPU by voxel-based morphometry (VBM) and tract-based spatial statistics (TBSS) methods, and the moderating analysis was conducted by PROCESS using SPSS software. VBM analysis found an inverse correlation between the GMV of the anterior cingulate gyrus (ACC) and right fusiform gyrus (FFG) with PMPU ( P FDR < 0.05), and TBSS analysis revealed that fractional anisotropy (FA) in the body of the corpus callosum was negatively correlated with PMPU. The correlation between PMPU and depressive symptoms was moderated by the GMV of the ACC. These results suggest that the GMV of the ACC and right FFG, as well as FA in the body of the corpus callosum, was related to PMPU, and we further found that increased GMV of the ACC could reduce the relationship between PMPU and depressive symptoms in college students.